The world of fear in the Hillarion Pavliuk’s novel “The madman’s dance” - Grebeniuk, T. V.; Гребенюк, Тетяна Володимирівна (Lviv-Toruń : Liha-Pres, 2020)
Science-fiction literature is one of the specific genre and meta-genre systems that are not yet represented by the bestsellers in the field of Ukrainian mass literature. There is a large number of writers and works of Ukrainian fiction genre but it is mostly represented by fantasy books of the writers of the “first row” who have become popular in other genres and remain in the public eye. Those are, such as Y. Vinnychuk, V. Yeshkileva, O. Zabuzhko, O. Irvanets, G. Pogutyak and others. Nevertheless, science-fiction literature in Ukraine can be considered as a full fledged independent branch of creative arts. It has its own tradition, which is rooted in the poetics of the Kyiv-Pechersk Pateric and in the chronologically closer epochs, represented by the names of V. Vinnychenko, V. Vladko, O. Ilchenko, Yu. Smolich, G. Shkurupii, M. Trublaini, O. Berdnyk and others. Today “the fantastic” in Ukrainian literature is represented by O. Avramenko, V. Arenyev, Y. Bedzik, T. Vinokurova-Sadichenko, L. Deresh, Y. Dubynyanska, V. Yeshkilev, O. Irvanets, Dara Kornii, O. Levchenko, T. Lytovchenko, I. Pavlyuk, R. Radutny, M. Sokolyan, S. Taratorina, V. Tarnavskyi, O. Shynkarenko, V. Ivchenko, M. Kidruk and others.